Pengembangan E-LKPD Berbasis Discovery Learning pada Materi Teks Negosiasi Siswa Kelas X SMAN 1 Sarolangun Provinsi Jambi - Weny Septiani; Amril Amir (Publikasi Indonesia, 2023)
This study aims to describe how the design of the E-LKPD model is based on discovery learning, how to develop E-LKPD based on discovery learning and analyze the feasibility of discovery learning-based E-LKPD on negotiation text material to be developed at SMA Negeri 1 Sarolangun. This type of research is development research that adopts 4D development (Define, Design, Developmet, Disseminate) with modifications, without disseminate stage (deployment). The research and development steps are problem identification and analysis, product design, development, and validation. Research instruments in the form of teacher interview sheets, student needs analysis questionnaires, material expert validation sheets, media experts analyzed using a likert scale. The results showed that: (1) a discovery learning-based E-LKPD has been designed with development on aspects of negotiation text material, (2) after the design is carried out, then a discovery learning-based E-LKPD is developed on the negotiation text material through liveworksheets, (3) the feasibility of developing a discovery learning-based E-LKPD which is assessed by the material expert is in the very valid category (91.2%) or is declared suitable for use and according to media experts The developed E-LKPD is in the valid category (87.5%) or declared eligible for use. Thus, it can be concluded that discovery learning-based E-LKPD can be used in the learning process in high school.